Minimally Complex Nucleic Acid Feedback Control Systems for First Experimental Implementations ⁎Funded by BBSRC/EPSRC (BB/M017982/1) and the EPSRC & BBSRC Centre for Doctoral Training in Synthetic Biology (EP/L016494/1). Issue 2 (2020) - Paulino, Nuno M.G.; Foo, Mathias; de Greef, Tom F.A.; Kim, Jongmin; Bates, Declan G.
Abstract: Chemical reaction networks based on catalysis, degradation, and annihilation may be used as building blocks to construct a variety of dynamical and feedback control systems in Synthetic Biology. DNA strand-displacement, which is based on DNA hybridisation programmed using Watson-Crick base pairing, is an effective primitive to implement such reactions experimentally. However, experimental construction, validation and scale-up of nucleic acid control systems is still significantly lagging theoretical developments, due to several technical challenges, such as leakage, crosstalk, and toehold sequence design. To help the progress towards experimental implementation, we provide here designs representing two fundamental classes of reference tracking control circuits (integral and state-feedback control), for which the complexity of the chemical reactions required for implementation has been minimised. The supplied 'minimally complex' control circuits should be ideal candidates for first experimental validations of nucleic acid controllers.